Compromised energy and macronutrient intake of ultra-endurance runners during a multi-stage ultra-marathon conducted in a hot ambient environment - Costa, R. J. S.; Swancott, A. J. M.; Gill, S.; Hankey, J.; Scheer, V.; Murray, A.; Thake, C. D. (International Journal of Sports Science, 2013)
Energy and macronutrient intake of ultra-endurance runners (UER n=74; control (CON) n=12) during a 5-days 225km multi-stage ultra-marathon (MSUM) in the heat (Tmax 32-40°C), were determined through dietary recall interview and analysed by dietary analysis software. Body mass (BM) and urinary ketones were determined pre- and post-stage. Recovery, appetite and gastrointestinal symptoms were monitored daily. Pre-stage BM, total daily energy (overall mean: 3348kcal/day), protein (1.5g/kgBM/day), carbohydrate (7.5g/kgBM/day) and fat (1.4g/kgBM/day) intakes did not differ between stages in UER. CON presented a daily macronutrient profile closer to benchmark recommendations than UER. Carbohydrate intake pre-stage (102g), during running (24g/h) and immediately post-stage (1.7g/kgBM), and protein intake post-stage (0.3g/kgBM) did not differ between stages, and were below benchmark recommendations in the majority of UER. Post-stage urinary ketones increased in UER as competition progressed (Stage 1: 16% vs. Stage 5: 32%). Gastrointestinal distresses and appetite suppression were reported by 85% and 72% of UER, respectively, along the MSUM. Correlations between subjective symptomology, energy and carbohydrate intakes were observed in UER (P<0.05). Sub-optimal macronutrient profile, carbohydrate intake, and recovery nutrition throughout the MSUM suggests energy quantity and quality may be compromised in ultra-runners along competition; indicating that specialised nutritional education may be beneficial in this population.